INDUKSI EMBRIO SOMATIK DARI TANAMAN KAKAO ADAPTIVE ACEH MENGGUNAKAN EKSPLAN BUNGA SERTA ZAT PENGATUR TUMBUH PICLORAM - Zuyasna Zuyasna; Siti Hafsah (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
In order to fulfill the cocoa revitalization program, relatively large quantities of seedling are needed. Tissue culture is one of the alternative techniques for vegetative propagation that produce the large numbers of seedlings and uniform in a relatively short time, and also does not depend on the season. A preliminary study to induce callus and embryo somatic cocoa clones adaptive in Aceh has been carried out using immature flower parts of cocoa. The result showed that picloram was able to produce somatic embryos of staminode of various explants. Callus growth began to appear after two weeks on staminode, and then were subcultured into the same medium to produce secondary somatic embryos.